Acute effect of running exercise on physiological Achilles tendon blood flow. (17th April 2017) - Risch, L.; Cassel, M.; Mayer, F.
Abstract : Sonographically detectable intratendinous blood flow (IBF) is found in 50%–88% of Achilles tendinopathy patients as well as in up to 35% of asymptomatic Achilles tendons (AT). Although IBF is frequently associated with tendon pathology, it may also represent a physiological regulation, for example, due to increased blood flow in response to exercise. Therefore, this study aimed to investigate the acute effects of a standardized running exercise protocol on IBF assessed with Doppler ultrasound (DU) "Advanced dynamic flow" in healthy ATs. 10 recreationally active adults (5 f, 5 m; 29±3 years, 1.72±0.12 m, 68±16 kg, physical activity 206±145 minute/wk) with no history of AT pain and inconspicious tendon structure performed 3 treadmill running tasks on separate days (M1‐3) with DU examinations directly before and 5, 30, 60, and 120 minutes after exercise. At M1, an incremental exercise test was used to determine the individual anaerobic threshold (IAT). At M2 and M3, participants performed 30‐ minute submaximal constant load tests (CL1 /CL2 ) with an intensity 5% below IAT. IBF in each tendon was quantified by counting the number of vessels. IBF increased in five ATs from no vessels at baseline to one to four vessels solely detectable 5 minutes after CL1 or CL2 . One AT had persisting IBF (three vessels) throughout all examinations. Fourteen ATs revealed no IBF at all. Prolonged running led to a physiological, temporary appearance of IBF in 25% of asymptomatic ATs. To avoid exercise‐induced IBF in clinical practice, DU examinations should be performed after 30 minutes of rest.